Piezoelectric RF resonant voltage amplifiers for IoT applications - Ruochen Lu; Manzaneque, Tomas; Breen, Michael; Anming Gao; Songbin Gong (2016 IEEE MTT-S International Microwave Symposium (IMS), 2016)
This paper reports the design and development of aluminum nitride (AlN) piezoelectric RF resonant voltage amplifiers for Internet of Things (IoT) applications. These devices can provide passive and highly frequency selective voltage gain to RF backends with a capacitive input to drastically enhance sensitivity and to reduce power consumption of the transceiver. Both analytical and finite element models (FEM) have been utilized to identify the optimal designs. Consequently, an AlN voltage amplifier with an open circuit gain of 7.27 and a fractional bandwidth (FBW) of 0.11 % has been demonstrated. This work provides a material-agnostic framework for analytically optimizing piezoelectric voltage amplifiers.